2014
DOI: 10.1161/circulationaha.113.006800
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Interleukin-1β Decreases Aneurysm Formation and Progression in a Novel Model of Thoracic Aortic Aneurysms

Abstract: Background Thoracic aortic aneurysms (TAAs) are common, but experimental TAA models are limited and the role of interleukin-1β (IL-1β) is undetermined. Methods and Results IL-1β protein was measured in human TAAs and control aortas, and IL-1β protein was increased ≈20-fold in human TAAs. To develop an experimental model of TAAs, 8- to 10-week-old male C57Bl/6 mice (wild type [WT]) underwent thoracotomy with application of periadventitial elastase (WT TAA) or saline (WT control; n=30 per group). Elastase trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 23 publications
3
118
0
Order By: Relevance
“…So far, all of these facts indicate a very finely tuned inflammatory process in human aortic aneurysms and therefore the recently postulated prognostic value for phosphorylation of c-kit and downstream targets in aneurysm formation fits well in this concept [20]. In this context, recent studies reported that the inhibition of cytokine IL-1 attenuates experimental development of aortic aneurysm [21], as well as activation of TGF-signalling [22]. Future studies should address the exact characterization and cellular imaging of the inflammatory cells, that is, T-cells, macrophage subpopulations, and so forth, in order to better understand their specific contribution during development of human aneurysms.…”
Section: Discussionmentioning
confidence: 72%
“…So far, all of these facts indicate a very finely tuned inflammatory process in human aortic aneurysms and therefore the recently postulated prognostic value for phosphorylation of c-kit and downstream targets in aneurysm formation fits well in this concept [20]. In this context, recent studies reported that the inhibition of cytokine IL-1 attenuates experimental development of aortic aneurysm [21], as well as activation of TGF-signalling [22]. Future studies should address the exact characterization and cellular imaging of the inflammatory cells, that is, T-cells, macrophage subpopulations, and so forth, in order to better understand their specific contribution during development of human aneurysms.…”
Section: Discussionmentioning
confidence: 72%
“…The thoracic and abdominal aorta contain cells of distinct embryologic origins [3]. Additionally, the thoracic aorta has greater elastin content and contains more prominent vaso vasora than the abdominal aorta [4][5][6]. Current nonsurgical therapy for AAA and TAA is aimed at preventing further dilation and includes risk factor reduction and b-adrenergic blockade (for TAA), both with limited efficacy [1,7].…”
mentioning
confidence: 99%
“…In the anakinra and etanercept experiments, the pregnant mice received i.p. injections of 100 mg/dam control IgG, 300 mg/dam anakinra, 100 mg/dam etanercept, or a combination of anakinra and etanercept at the mentioned doses (McCall et al 2012, Johnston et al 2014.…”
Section: Rt-pcr Analysismentioning
confidence: 99%